PENGENALAN EVALUASI PROGRAM PEMBELAJARAN MENGGUNAKAN MODEL STAKE - Kamal; Rahmadhani, Rahmi (TEKNOS: Jurnal Pendidikan dan Teknologi, 2024)
Evaluation of the stake model program is a process carried out to measure the effectiveness, success and impact of the implementation of the stake model program in a particular context. The stake model program involves identifying, analyzing, and involving stakeholders in decision making and implementation of a program or project. The aim of this research is to comprehensively analyze the Stake evaluation model, starting from its meaning to how to use the Stake evaluation model in order to maximize various educational programs and provide recommendations to improve their quality. The research design used is the literature review method. Literature study (literature review) is research carried out by researchers by collecting a number of books, journals, articles, research results related to research problems and objectives. The stake evaluation model in carrying out evaluations emphasizes two basic things that must be present, namely description and judgment. These two basic things are further divided into three study objects in evaluation, namely antecedents, transactions, outcomes. The results of the analysis show that the stake model (countenance model) has several advantages, such as being comprehensive in collecting data, the evaluator has the freedom to collect data and translate it and can come up with new theories related to events in the field. While the disadvantage is that it is too subjective in its approach to collecting data, most data is qualitative in nature and costs a lot of money.